Conditions, constraints and contracts: On the use of annotations for policy modeling - Bottoni, Paolo; Navigli, Roberto; Parisi-Presicce, Francesco (Electronic Communications of the EASST, 2016)
Organisational policies express constraints on generation and processing of resources. Application domains, however, rely on transformation processes, which are in principle orthogonal to policy specifications, so that domain rules and policies may evolve in a non-synchronised way. In previous papers, we proposed annotations as a flexible way to model aspects of some kinds of policy. Annotations could be used to impose constraints on domain configurations, and we showed how to derive application conditions on transformations, and how to annotate complex patterns. We extend the approach here in different directions: we allow domain model elements (individual resources or collections thereof) to be annotated with collections of elements; we propose an original construction to solve the problem of orphan annotations, when annotated resources are consumed; we introduce a notion of contract, used by a policy to impose additional pre-conditions and postconditions on rules for deriving new resources. We also show how contracts for refined rules can be derived from contract schemes defined on some rule kernel. We discuss a concrete case study of linguistic resources, annotated with information on the licenses under which they can be used. The annotation framework allows forms of reasoning such as identifying conflicts among licenses, enforcing the presence of licenses, or ruling out some modifications of a licence configuration.